ANALYSIS OF THE MAIN CHARACTER â€œDASIYAHâ€ AS A FEMINIST IN CIGARETTE GIRL NOVEL - RISMA KARTIKA DEWI (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2017)
The aims of this research to describe: 1) The personality of Dasiyah in Cigarette Girl Novel, 2) The struggle of gender equality in Cigarette Girl Novel, 3) The social condition in Cigarette Girl Novel. This research used qualitative method. Qualitative method is a research procedure that results in description data in form of words. The data of this research is Cigarette Girl Novel by Ratih Kumala. This research used extrinsic approach. Technique of collecting data is used by reading novel and analyzing document. The technique of analyzing data is using content analysis of three elements, which are reducing data, data presenting data, drawing conclusion. Based on the result of the research can be concluded: 1) Dasiyah’s personality which are diligence, initiative, responsible, it was a proactive personality. 2) The struggle of gender equality in Cigarette Girl Novel is a fight against all forms of gender injustice such as stereotype, women marginalization, jobs subordination, and household violence. 3) Social conditions which were described in Cigarette Girl Novel were divided into three eras, which was social condition in 1945, social condition in 1965, and social condition in 2000. Keywords: Feminist, Novel, cigarette girl Novel, Dasiyah